Penerapan Arsitektur Tropis pada Gedung Sekolah RA Al-Ikram di Medan Sunggal - Lubis, Nifana Riza R.; Saraswaty, Rina (Universitas Medan Area, 2025)
Indonesia has a tropical climate, Indonesia also has high rainfall, high humidity and is exposed to intensive sunlight. Indonesia faces unique challenges in creating buildings that are not only aesthetic, but also functional and comfortable for its occupants, so tropical architecture plays an important role in reducing heat accumulation and optimizing indoor air ventilation. Tropical Architecture is a design that focuses on and adapts to tropical climate conditions, such as in Indonesia. Therefore, tropical architecture in Indonesia needs to be considered, one of which is in the city of Medan, North Sumatra province, Indonesia. This study was conducted with the aim of analyzing the application of tropical architecture to the Ra Al - Ikram school building. This building is located in the Medan Sunggal sub-district using several applications of tropical architecture as a solution to problems in tropical climates today. where in the design of the Ra Al - Ikram school building, it aims to analyze the application of tropical architecture in Medan Sunggal by covering the principles of Tropical Architecture